Inhibitory effects of flavonoids isolated from Sophora flavescens on indoleamine 2, 3-dioxygenase 1 activity. (1st January 2019) - Kwon, Mincheol; Ko, Sung-Kyun; Jang, Mina; Kim, Gun-Hee; Ryoo, In-Ja; Son, Sangkeun; Ryu, Hyung Won; Oh, Sei-Ryang; Lee, Won-Kyu; Kim, Bo Yeon; Jang, Jae-Hyuk; Ahn, Jong Seog
Abstract: Indoleamine 2, 3-dioxygenase 1 (IDO1), a tryptophan catabolising enzyme, is known as a tumour cell survival factor that causes immune escape in several types of cancer. Flavonoids of Sophora flavescens have a variety of biological benefits for humans; however, cancer immunotherapy effect has not been fully investigated. The flavonoids (1–6) isolated from S. flavescens showed IDO1 inhibitory activities (IC50 4.3– 31.4 µM). The representative flavonoids (4–6 ) of S. flavescens were determined to be non-competitive inhibitors of IDO1 by kinetic analyses. Their binding affinity to IDO1 was confirmed using thermal stability and surface plasmon resonance (SPR) assays. The molecular docking analysis and mutagenesis assay revealed the structural details of the interactions between the flavonoids (1–6) and IDO1. These results suggest that the flavonoids (1–6) of S. flavescens, especially kushenol E (6 ), as IDO1 inhibitors might be useful in the development of immunotherapeutic agents against cancers. Graphical Abstract: